Experimental Verification of Seismic Strengthening by Wing Wall Installation for RC Buildings with Substandard Beam-column Joints. (2017) - Sanada, Yasushi; Li, Yuebing; Maekawa, Koki
Abstract: A series of laboratory tests was conducted to experimentally evaluate the seismic behavior and performance of the 1/2.5 scale partial moment-resisting frame specimens representing a moderately damaged building by the 2013 Bohol, Philippines earthquake. The un-strengthened specimen exhibited a lower seismic resistance compared to the design calculation under a beam yield mechanism. R/C wing walls were applied to the exterior or interior column face of two un-strengthened specimens to upgrade the seismic performance. Effectiveness of the seismic strengthening by the wing wall installation was verified through comparing the experimental results among the un-strengthened and strengthened specimens.